Unusual Chemistry of the C-H-N-O System under Pressure and Implications for Giant Planets - Naumova, Anastasia S; Lepeshkin, Sergey V; Bushlanov, Pavel V; Oganov, Artem R (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2021)
C-H-N-O system is central for organic chemistry and biochemistry and plays a major role in planetary science (dominating the composition of "ice giants" Uranus and Neptune). The inexhaustible chemical diversity of this system at normal conditions explains its role as the basis of all known life, but the chemistry of this system at high pressures and temperatures of planetary interiors is poorly known. Using evolutionary algorithm USPEX, we performed an extensive study of the phase diagram of the C-H-N-O system at pressures of 50, 200, and 400 GPa and temperatures up to 3000 K. Seven novel thermodynamically stable phases were predicted, including quaternary polymeric crystal C H N O and several new N-O and H-N-O compounds. We describe the main patterns of changes in the chemistry of the C-H-N-O system under pressure and confirm that diamond should be formed at conditions of the middle-ice layers of Uranus and Neptune. We also provide the detailed CH -NH -H O phase diagrams at high pressures, which are important for further improvement of the models of ice giants, and point out that current models are clearly deficient. In particular, in the existing models, Uranus and Neptune are assumed to have identical composition, nearly identical pressure-temperature profiles, and a single convecting middle layer ("mantle") made of a mixture of H O/CH /NH in the ratio of 56.5:32.5:11. Here, we provide new insights, shedding light into the difference of heat flows from Uranus and Neptune, which require them to have different compositions, pressure-temperature conditions, and a more complex internal structure.